HFE C282Tyr homozygotes with serum ferritin concentrations below 100ug/L are at low risk of hemochromatosis - Allen, K.; Bertalli, N.; Osborne, N.; Constantine, C.; Delatycki, M.; Nisselle, A.; Nicoll, A.; Gertig, D.; McLaren, C.; Giles, G.; Hopper, J.; Anderson, G.; et al. (John Wiley & Sons Inc., 2010)
HFE-associated hereditary hemochromatosis (HH) is a genetic predisposition to iron overload and subsequent signs and symptoms of disease potentially affecting around 80,000 in Australia and almost one million people in the USA. Most clinical cases are homozygous for the C282Y mutation in the HFE gene, with serum ferritin (SF) concentration >1000 μg/L the strongest predictor of cirrhosis. The optimal treatment regimen for those with SF concentrations above the normal range but <1000 μg/L is unknown. We assessed HFE mutations in a prospective cohort of 31,192 participants of northern European descent, aged 40–69 years. An HFE-stratified random sample of 1438 participants including all C282Y homozygotes with iron studies 12 years apart were examined by physicians blinded to HFE genotype. All previously undiagnosed C282Y homozygotes (35 male, 67 female) and all HFE wild-types (131 male, 160 female) with baseline and follow-up SF concentrations <1000 μg/L were assessed for HH-associated signs and symptoms including abnormal second/third metacarpophalangeal joints (MCP 2/3), raised liver enzymes, hepatomegaly, and self-reported liver disease, fatigue, diabetes mellitus, and use of arthritis medication. The prevalence of HH-associated signs and symptoms was similar for C282Y homozygotes and HFE wild-types for both normal and moderately elevated SF concentrations. The maximum prevalence difference between HFE genotype groups with moderately elevated SF was 11% (MCP 2/3 95% CI (−6%, 29%), p=0.22) and for normal SF was 6% (arthritis medicine use, 95% CI (−3, 16), p=0.11).